2003
DOI: 10.1017/s0950268803008720
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey of anti-group A rotavirus IgM in UK adults

Abstract: SUMMARYRotaviral associated disease of infants in the UK is seasonal and infection in adults not uncommon but the relationship between these has been little explored. Adult sera collected monthly for one year from routine hospital samples were screened for the presence of anti-group A rotavirus immunoglobulin M class antibodies as a marker of recent infection. Anti-rotavirus IgM was seen in all age groups throughout the year with little obvious seasonal variation in the distribution of antibody levels. IgM con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
(36 reference statements)
1
17
0
Order By: Relevance
“…This is confirmed by community studies showing that rotavirus infection was shed by mild sporadic cases of diarrhea not necessitating hospitalization or asymptomatic subjects, spanning all ages [22]. In the UK, rotavirus-specific IgM was detected in the normal adult population with no seasonal trend [23], suggesting constant circulation of the virus among adults independent on the winter peak of disease typical for children. Although immunity to rotavirus gastroenteritis has been considered to be life-long, adults might play a role of healthy carriers and reservoir for rotavirus [24].…”
Section: Serotypes Genotypes and Immunitysupporting
confidence: 53%
“…This is confirmed by community studies showing that rotavirus infection was shed by mild sporadic cases of diarrhea not necessitating hospitalization or asymptomatic subjects, spanning all ages [22]. In the UK, rotavirus-specific IgM was detected in the normal adult population with no seasonal trend [23], suggesting constant circulation of the virus among adults independent on the winter peak of disease typical for children. Although immunity to rotavirus gastroenteritis has been considered to be life-long, adults might play a role of healthy carriers and reservoir for rotavirus [24].…”
Section: Serotypes Genotypes and Immunitysupporting
confidence: 53%
“…Tests for sensitivity and specificity were done; sera from "presumed low risk" (North American) children were used as "nega- Such persistence has also been noted previously (Casemore 1987;Ungar et al 1989), and in some viral infections (Cox & Medley 2003). A further report from Newman et al (1999) described fecal studies on children in the same area, sampled over a four-year period, and confirmed evidence of possible recurrent or repeat symptomatic infection as well as asymptomatic cases.…”
Section: Early Worldwide Studiesmentioning
confidence: 86%
“…Enteroviruses are generally ubiquitous, even in areas with high levels of hygiene and water quality, although sub-types vary in frequency of reporting geographically and temporally. Antibody studies generally reflect this ubiquity (Payment 1991;Cox & Medley 2003). Data from a study by Jiang and others supports a protective role for antibody to rotavirus, or as a correlate of protective immunity (Jiang et al 2002).…”
Section: Other Virusesmentioning
confidence: 98%
See 1 more Smart Citation
“…Secondly, we observed year-round circulation of rotaviruses in the country, with increased incidence in the winter season and unexpected peaks preceding the rotavirus seasons. An investigation of the presence of anti-rotavirus group A IgM antibodies in adults conducted in the United Kingdom [43] has shown a high titer of antibodies all year round, despite their seasonal distribution in the child population. Thus, this might suggest the year-round circulation of rotaviruses and an asymptomatic or milder course of rotavirus disease during the summer months, which may be a consequence of herd immunity acquired during the winter months.…”
Section: Epidemiology Of Rotavirus Infectionmentioning
confidence: 99%